Animals in our days : a book of stories - Makhzanjī, Muḥammad (Middle East literature in translation., 2022)
"A themed collection of short stories about animals, which offers a striking example of environmentally concerned literature from the Arab world, by an Egyptian author with a keen and sensitive eye for the behavior of animals-especially homo sapiens"--